AB1341-HPR FEASIBILITY OF THE BACK AND FORTH SCHOOL BOOKLET, A SHARED SELF MANAGEMENT INSTRUMENT FOR YOUNG CHILDREN WITH JUVENILE IDIOPATHIC ARTHRITIS (JIA) AT SCHOOL. (2nd June 2020) - Cappon, J.; Van Rossum, M.; Littooij, E.; Van der Leeden, M.
Abstract : Background: Young children with JIA have to cope with pain and fatigue during schooldays, facing problems with writing, climbing stairs, physical education and playing outside. 1 They need to develop age-appropriate self management skills, encouraged by their parents and teachers in a therapeutic alliance with the health professional team. 2 For this purpose a shared management tool, called the "Back and Forth Schoolbooklet"(B&FS), is developed, containing 1) Educational pages about JIA, pain and fatigue management 2) Diary pages with a colour-in puppet for expressing location and amount of pain, spaces for writing alternatives for limited activities, feedback spaces for parents and teachers and a self-evaluation scale of general well-being for the child. Children, parents and teachers are instructed how to use the booklet by therapists during outpatient rehabilitation. Structured evaluation of the use of the instrument is necessary to improve its applicability and effectiveness. Objectives: To study the feasibility, defined as practical and experienced applicability and effectiveness, of the B&FS. Methods: Pilot feasibility study with a mixed-method design. Parents, teachers, therapists and children with JIA were invited to fill in questionnaires after using the booklets in school. Adults had to sign informed consent. Practical applicability was assessed by multiple choice questions on duration and frequency of use. Used diary items and pages were counted in returned booklets. Experienced applicability and effectiveness were assessed by open-ended questions and 5 points Likert scales. Topics were experienced barriers, facilitators and benefits using the mentioned items of the booklets. Practical applicability was analysed descriptively. Atlas-ti8 was used for analysing and coding the answers on the open-ended questions using a thematic approach. Results: Eight children(4-8 years) used the booklets. Six parents of six children, four therapists and four teachers signed informed consent and answered questionnaires. Six booklets were returned. Practical applicability : Five children used booklets for a period of 2 to > 12 week, almost every day. One child stopped in the first week. Counting diary pages confirmed every day or every second day appropriate use of the color-in puppet and spaces for parents and teachers. Experienced applicability : Identified themes were: child-friendly, easy and providing a clear guide for the daily school situation. Themes as: daily obligation, unwillingness of the child, lack of motivation or time of the parents or teachers and insufficient instruction illustrated experienced barriers for the use of the booklet. Effectiveness : Identified themes: 1) Children express themselves better about feelings of pain and fatigue, 2) Parents and teachers appreciate more insight into how the child feels and 3)Teachers feel provided with guidance in the interaction with the child 4) Children feel more secure to express itself at school and 4) Parents are more relaxed about the schoolsituation. Likertscales showed that more than 75% of the users would advise the B&FS to other parents, teachers and therapists. Conclusion: The Back & Forth School booklet is a feasible shared management instrument to support young children with JIA in the school situation. A less rigid daily routine and sufficient instruction can improve the experienced applicability. References: [1]Tong, A. Children's experiences of living with juvenile idiopathic arthritis. Arthritis Care Res. 2012;64(9):1392-1404. [2]Kieckhefer, G Supporting development of children with chronic conditions: from compliance toward Shared management. Pediatr Nursing, 2000;26(4). Acknowledgments: Children, parents, teachers and therapists Disclosure of Interests: None declared